Exploring the Professional Development Pathways of Graduates from the Master’s Programs in Education: Inputs for Curricular Enhancement - Sanchez, Joje Mar Perino; Abella, Rongie Cabico; Cadosales, Maria Nancy Quinco; Olvido, Michelle Mae Jugasan; Boholano, Helen Bihag (FKIP Universitas Lampung, 2023)
Exploring the Professional Development Pathways of Graduates from the Master's Programs in Education: A Tracer Study in a Center of Excellence. Objectives: This tracer study aimed to trace the graduates of the master’s programs in Teacher Education in a center of excellence in Central Visayas, Philippines. Methods: Using a validated tracer study tool, the researchers obtained data from 136 respondents and analyzed these data through descriptive statistical and thematic analyses. Findings: Findings revealed that they became better after receiving the master's degree, where the university master's attributes are evident among them. They attained crucial attributes, developed complex skills, and were promoted to a higher teaching rank. Though they improved, they still recommended that the center of excellence employ flexible and integrative learning, where certifications and current trends and issues are embedded. Conclusion: In conclusion, the education master's program has provided instruction and a learning environment where students become proficient teachers and workers in their respective teaching stations. Future researchers may venture into other aspects of the graduates to include in tracer studies. Keywords: masters programs, center of excellence, teacher education, tracer studyDOI: http://dx.doi.org/10.23960/jpp.v13.i2.202351